The Potential Roles of Magnetic Resonance Spectroscopy and Perfusion- Weighted Imaging in the Grading of Cerebral Gliomas - A. Bakan, Ayse; Alkan, Alpay (Current Medical Imaging, 2017)
Recent advances in the treatment of cerebral gliomas have increased the demand for diagnosis by means of neuroimaging in order to assist in treatment planning and prognosis. Advanced magnetic resonance (MR) imaging techniques, including MR spectroscopy (MRS) and MR perfusion, have proved invaluable in evaluating key pathological features of gliomas. MRS provides a broad range of information about cell membrane proliferation, neuronal integrity, energy metabolism, and necrosis of tumor tissue, while perfusion MR imaging provides valuable information about tumor neoangiogenesis. Together these imaging techniques aid in the grading of a glioma, a necessary step before planning a course of treatment. This report provides an up-to-date review of brain MRS and MR perfusion techniques and discusses their potential roles in glioma grading.
Keywords: glioma